Product Quality Control of Shoes Using Statistical Process Control and Fault Tree Analysis Methods - Inggit Marodiyah; Noor Zakki Kurniawan Ujisantoso (International Journal on Orange Technologies, 2026)
PT X is a shoe manufacturing company in Sidoarjo, East Java that produces shoes. The company still faces a product defect rate that exceeds the quality standard of 5%, with an average defect rate of 8.11% so that systematic quality control is needed. This study aims to analyze the dominant types of shoe product defects and identify their root causes. The Statistical Process Control (SPC) method is a method used to ensure that each production process runs according to standards so that the resulting product meets consumer quality requirements, while Fault Tree Analysis (FTA) is a top-down analysis that traces cause-and-effect relationships to break down peak events to their root causes, and provide recommendations for improvement. Research data was obtained through observation, interviews, and production and defect data for the period May–October 2025. The results showed that the most dominant type of defect in the shoe production process was untidy stitching of 10,326 pieces. The causes came from human and machine factors, such as lack of operator accuracy, machine setting errors, and worn machine component conditions that caused product defects. To reduce this, recommendations for improvements are provided, such as improving operator skills and regular machine maintenance and adjustments.